2019
DOI: 10.4236/ajibm.2019.94064
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Forecasting of Ghana’s Inflation Volatility

Abstract: In this paper, we assessed volatility of Ghana's inflation rates for 2000 to 2018 using the auto-regressive conditionally heteroskedasticity (ARCH), generalized ARCH (GARCH), and the exponential GARCH (EGARCH) models. The inflation data were obtained from the Ghana Statistical Service (GSS). The proposed model should be able to provide projections of inflation volatility from 2019 and beyond. The results showed that higher order models are required to properly explain Ghana's inflation volatility and the EGARC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…We find a bidirectional relationship between stock market development and inflation. Similar results were found for African countries where inflation brought volatility to the capital market (Iddrisu et al, 2019), and European countries (Fuinhas et al, 2019). Any economy with high inflation refers to a time of instability.…”
Section: Discussionsupporting
confidence: 74%
“…We find a bidirectional relationship between stock market development and inflation. Similar results were found for African countries where inflation brought volatility to the capital market (Iddrisu et al, 2019), and European countries (Fuinhas et al, 2019). Any economy with high inflation refers to a time of instability.…”
Section: Discussionsupporting
confidence: 74%
“…A plethora of literature has studied volatility in some time series variable such as crude oil price (Suleiman et al, 2015Alhassan & Kilishi, 2016Muhammed & Faruk, 2018;Zhang et al, 2019;Nguyen & Walther, 2020;;Boitumelo et al, 2020), exchange rate (Kuhe & Agaigbe, 2018;Abdullah et al, 2017;Okoro & Osisiogu, 2017;Dritsaki, 2019), stock prices (Al Rahahleh & Kao, 2018;Iwada et al, 2018;Lin, 2018;Aliyev et al, 2020), inflation (Fwaga et al, 2017;Nyoni, 2018;Iddrisu et al, 2019) amongst others. Modeling PVCO by some authors has reported varying outcomes over the years.…”
Section: Introductionmentioning
confidence: 99%